Answer:
A and C is correct.
Explanation:
![\text{Rational Equation: }(4)/(x+6)+(1)/(x^2)=(x+10)/(x^3+6x^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/rf8jrjf5zthlaieje1wfjn3oz3xprtv89r.png)
First we simplify this equation (-1 + x^2)/(x (6 + x))
![(x^2-1)/(x(x+6))=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/sn56u9nx0gd7ar91ripj235687ni9u9dgt.png)
Solution set: x=1,-1
We have to check all option which is solution of above equation.
A) x=1, we will put x=1 into equation both sides.
![\text{Left Side:} \Rightarrow (4)/(x+6)+(1)/(x^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/wpw5x959jymzvm15spb8t4dafl6kj9arsd.png)
![\Rightarrow (4)/(1+6)+(1)/(1^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/86tpxi38s7d6b7l4y13ukmcv4o2dt38bpa.png)
![\Rightarrow (11)/(7)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/trjaiotgtumipg25exu6uh7miw2acfac2j.png)
![\text{Right Side:} \Rightarrow (x+10)/(x^3+6x^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/p4qge7c6cxfdwvwg4dmx76w19y9f3pzn2u.png)
![\Rightarrow (1+10)/(1^3+6* 1^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/uxxw2i96waza3557ozh61y6kjycjpc1z8s.png)
![\Rightarrow (11)/(7)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/trjaiotgtumipg25exu6uh7miw2acfac2j.png)
![\text{Left Side}=\text{Right Side}=(11)/(7)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ktlsct6tdg0lwvv63ux8dv1mf8d7g0vip4.png)
Thus, x=1 is a solution.
C) x=-1, we will put x=-1 into equation both sides.
![\text{Left Side:} \Rightarrow (4)/(x+6)+(1)/(x^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/wpw5x959jymzvm15spb8t4dafl6kj9arsd.png)
![\Rightarrow (4)/(-1+6)+(1)/((-1)^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/5uu452kuq6ew3by12d4s4hpyr7proutdqs.png)
![\Rightarrow (9)/(5)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/c3awve0xsuoawpjyflxmoq7ckbw5wksjkp.png)
![\text{Right Side:} \Rightarrow (-1+10)/(-1^3+6(-1)^2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/d6jll3exmc262upgtu3sn5mel3igsczyij.png)
![\Rightarrow (9)/(-1+6* 1)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/kjin3hwbwilh6fgdkodjc7zplhx94ifdzs.png)
![\Rightarrow (9)/(5)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/c3awve0xsuoawpjyflxmoq7ckbw5wksjkp.png)
![\text{Left Side}=\text{Right Side}= (9)/(5)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/g9iofd7g0i6gcjuzrj11k3gjhmvhxmh675.png)
Thus, x=-1 is a solution.
Thus, A and C is correct.